Estrategias de fidelización para la agencia mano negra de Latacunga. - Morales Suárez, William Bolívar (2023)
Customer loyalty is essential for a company to survive financially and within marketing it is one of the most accessible strategies because it does not need to invest larger sums of money as in the acquisition of new customers. Based on these arguments, the present investigation aims to develop strategies that allow increasing the loyalty of its clients in the Mano Negra Agency of the city of Latacunga, with the purpose of reinforcing the knowledge that the company possesses. Focused on the stated objective, an inductive research was developed with a quantitative approach, field and documentary design with a cross-sectional and descriptive level, where surveys were carried out on 174 customers who bought on more than one occasion in the company, the questionnaire consisted of three sections, demographic data, influential factors in the purchase decision and loyalty strategies, it was carried out through a stratified sampling grouping the population in the eight product lines as established in the business and it was concluded in nine main strategies that should be focused for to be able to retain customers, which are: knowing the customer's perception of the product, coordination between company personnel, physical and digital sales tools, fluid communication, effective solutions to problems, personalized treatment, innovation and surprise, privileged attention and benefits according to the needs of the client, all this supported by Alcaide (2015) as a benchmark in customer loyalty, a moderately significant degree of relationship was also evidenced between the variables studied.